Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

f(x)= -1/4(x-1)^2- 3
I dont understand how to figure this question out, i ned the vertex, axis of symmetry, and the zeros.


Sagot :

f(x) = -1/4(x - 1)² - 3
f(x) = -1/4(x - 1)(x - 1) - 3
f(x) = -1/4(x² - x - x + 1) - 3
f(x) = -1/4(x² - 2x + 1) - 3
f(x) = -1/4(x²) + 1/4(-2x) + 1/4(1) - 3
f(x) = 1/4x² + 1/2x + 1/4 - 3
f(x) = 1/4x² + 1/2x - 2 3/4